Message encryption and authentication mechanism based on wireless physical layer key - Xingzhi,JINLiang LI; Zhou ZHONG; Yangming LOU (网络与信息安全学报)
In order to solve the problem of hidden key leakage in traditional high-level message authentication and passive eavesdropping in physical layer message authentication,a message encryption and authentication mechanism based on the characteristics of wireless physical layer was proposed.By extracting the characteristics of the wireless channel,the physical layer key was generated and the seed key was generated by combining the identity key.The key stream generator then generated the key stream to decrypt the message according to the extracted seed,protects the privacy of the transmitted data,and the final receiver authenticated the authenticity and integrity of the received message through the CRC verification result.Simulation results show that the proposed method has better performance in preventing passive eavesdropping and active attack,and the randomness of key stream is greatly improved and the rate of authentication leak detection is reduced by half.